2010
DOI: 10.1007/s12052-010-0243-z
|View full text |Cite
|
Sign up to set email alerts
|

Characters Are Key: The Effect of Synapomorphies on Cladogram Comprehension

Abstract: Cladograms, phylogenetic trees that depict evolutionary relationships among a set of taxa, are one of the most powerful predictive tools in modern biology. They are usually depicted in one of two formats-tree or ladder. Previous research (Novick and Catley 2007) has found that college students have much greater difficulty understanding a cladogram's hierarchical structure when it is depicted in the ladder format. Such understanding would seem to be a prerequisite for successful tree thinking. The present resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
0
24
0
2
Order By: Relevance
“…Figure 2 shows the scoring rubric that was used for part A of the PhAT, which connects to the idea that having synapomorphies displayed on branches allows students to understand trees better (Novick et al ., 2010). In part A, students were asked to map the evolution of large canine teeth, expanded metatarsals, and large incisors onto two different phylogenetic trees (alternative hypotheses) that were chosen out of the 15 possible phylogenetic trees for the relationships of rats, rabbits, dogs, and cats, with opossums as the outgroup (see Smith and Cheruvelil, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the scoring rubric that was used for part A of the PhAT, which connects to the idea that having synapomorphies displayed on branches allows students to understand trees better (Novick et al ., 2010). In part A, students were asked to map the evolution of large canine teeth, expanded metatarsals, and large incisors onto two different phylogenetic trees (alternative hypotheses) that were chosen out of the 15 possible phylogenetic trees for the relationships of rats, rabbits, dogs, and cats, with opossums as the outgroup (see Smith and Cheruvelil, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…A notable case of the latter comes from evolutionary biology, a field in which cognitive scientist Laura Novick and biologist Kefyn Catley have conducted extensive research about how students understand evolutionary relationships when different types of evolutionary tree representations are used (Catley and Novick, 2008; Novick et al ., 2010). Their research shows that the form of representation that is most commonly used in undergraduate biology texts leads to the least understanding of this important evolutionary concept.…”
Section: The Contributions Of Bermentioning
confidence: 99%
“…Novick et al (2010) found that including such characters on trees was critical to undergraduate students' ability to understand the structure (i.e., branching pattern) of the depicted phylogenies. Likewise, Ainsworth and Saffer's (2013) study points to the importance of synapomorphies in influencing children's understanding of cladograms.…”
Section: Include Characters On Cladograms To Indicate the Scientific mentioning
confidence: 99%